Progress report: dispersion and concentration of radioactive wastes by stream sediments - Sayre, William W., author; Guy, Harold P., author; Chamberlain, Adrian Ramond, author; Colorado State University, Civil Engineering Section, publisher (Colorado State University. Libraries, 1959)
The factors involved and the present status of research concerning disposal of radioactive wastes in natural streams are reviewed with respect to: 1) waste characteristics, 2) dispersion theory, 3) sorption by sediments, and 4) sediment transport. Some criteria for identifying potentially hazardous streams are discussed, areas where knowledge is deficient are pointed out, and recommendations for research are made. Evidence indicates that sorption of radiocontaminants by stream sediments is the rule rather than the exception. The extent of sorption is dependent upon a large number of variables-such as the nature of the sediment and the substance being sorbed, the available surface area, the concentration and types of solute in solution, time, and to a lesser extent temperature. The transport of sorbed radioactive components by fluvial sediments depends on factors such as the types and amounts of sediment supplied by the drainage area, channel and flow characteristics, the time distribution of stream flow, and channel controls. Pool and riffle type streams characterized by wide variations in discharge and containing large amounts of fine-grained sediments appear to be potentially the most dangerous type of stream with respect to the development of hazards arising from radiocontaminated sediments. Present knowledge is not adequate for the purpose of predicting the ultimate distribution of radioactive wastes in streams, particularly as affected by fluvial sediments. Considerable research and study will be required in all of the subject areas of this report before this situation can be improved materially. Certain deficiencies in knowledge and theory stand out. For example, there is a dearth of information in the literature on the quantities and physicochemical properties of low-level liquid wastes. Current theoretical, laboratory, and field knowledge of the mechanics of turbulent diffusion in cases involving a confined channel, net uptake by sediment, and net uptake by biota is entirely inadequate. The effect of some of the variables associated with sorption phenomena are not well understood. This is particularly so in complex sorption systems which include competing solutes, mixed sediments, and chemical additives such as detergents and electrolytes. Despite notable advances, some of the factors involved in sediment transport phenomena remain unresolved, and much of the associated theory is still in a stage of partial development.
CER59ARC26.
Keywords: Radioactive substances in rivers, lakes, etc.; Radioactive waste disposal; Radioisotopes in hydrology; Sediments (Geology)